S100A12 drives inflammatory and metabolic reprogramming in sepsis-associated acute kidney injury - Liu, Huanqin; Lv, Yanan; Xue, Qingjie; Shi, Jikui (Frontiers in Molecular Biosciences, 2026)
Sepsis-associated acute kidney injury (SA-AKI) is a severe complication of sepsis characterized by dysregulated inflammation, endothelial injury, and metabolic reprogramming. Among the numerous inflammatory mediators involved, S100 calcium-binding protein A12 (S100A12), a neutrophil-derived alarmin, has emerged as a key amplifier of receptor for advanced glycation end-products (RAGE) and toll-like receptor 4 (TLR4) signaling in this context. Through activation of these pathways, S100A12 drives inflammatory amplification, promotes cytokine release, pyroptotic and apoptotic cell death, endothelial dysfunction, and impaired tubular repair, thereby exacerbating renal injury. Experimental studies demonstrate that inhibition of S100A12 or blockade of its downstream signaling attenuates inflammation and tissue damage, whereas clinical evidence associates elevated circulating and urinary S100A12 levels with disease severity and adverse prognosis in sepsis. Collectively, current evidence positions S100A12 as both a mechanistic driver of inflammatory and metabolic reprogramming and a clinically actionable biomarker in SA-AKI. This review summarizes recent advances in the molecular biology and immunometabolic roles of S100A12 in SA-AKI, emphasizes its systemic versus kidney-specific effects, and discusses its translational potential as a biomarker and therapeutic target, highlighting opportunities and challenges for precision diagnostics and targeted therapies in sepsis-related organ injury.